PROBLEMS OF ENGINEERING EDUCATION IN MODERN RUSSIA: THE METHODS OF ANALYSIS AND WAYS OF SOLVING - Khazhismel G. Tkhagapsoyev; Martin M. Yakhutlov (Moscow Polytechnic University, 2016)
The article analyses the characteristics of the discourse (and its methodological errors) on the state and development issues of engineering education in modern Russia. It shows the preferred method of «case study» in the analysis of problems and search for ways to develop the engineering education. It proposes a number of concrete measures for the development of national engineering education, including the transition to more flexible format of Federal State Educational Standard, inter-university cooperation, empowering universities and specialized departments engaged in preparing engineers.